First Report on Microplastics Quantification in Poultry Chicken and Potential Human Health Risks in Pakistan - Muhammad Bilal; Madiha Taj; Habib Ul Hassan; Atif Yaqub; Muhammad Ishaq Ali Shah; Muhammad Sohail; Naseem Rafiq; Usman Atique; Mohammad Abbas; Saira Sultana; Umaiya Abdali; Takaomi Arai (Toxics, 2023)
Microplastics (MPs) are an emerging environmental health concern due to their widespread occurrence in food sources such as fish, meat, chicken, honey, sugar, salt, tea and drinking water, thereby posing possible risks to human health. This study aimed to observe the existence of MPs in the crop and gizzard of the farm chicken, a significant food source in Pakistan. Twenty-four chicken samples were taken from eight poultry farms across Punjab, Pakistan. A total of 1227 MP particles were found from 24 samples (crop and gizzards) originating from the 8 poultry farms. In all, 429 MP particles were found in 24 chicken crops, with a mean of 17.8 ± 12.1 MPs/crop. In contrast, 798 MP particles were found in 24 chicken gizzards, with a mean of 33.25 ± 17.8 MPs/gizzard. Comparatively larger particles, ranging between 300–500 µm, were more abundant (63%) than other considered sizes (300–150 µm [21%] and 150–50 µm [16%]). Additionally, fragments were the dominant type of shape in both sample types (crop [64%] and gizzard [53%]). The predominant colours of particles extracted from gizzards and crops were yellow (32%) and red (32%), respectively. Chemical characterisation of these particles detected four types of polymers: polyvinyl chloride (PVC) at 51.2%, followed by low-density polyethylene (LDPE) at 30.7%, polystyrene (PS) at 13.6% and polypropylene homopolymer (PPH) at 4.5%. In conclusion, we provide evidence for MPs in the gizzards and crops of farmed chickens which may originate from contaminated poultry feed. Only a few studies have been reported globally to assess MPs ingestion in chickens. The current study is the first report from Pakistan. It could be a valuable addition to support MPs literature to establish a relationship between MPs contamination and intake through the food chain.